Рецензія на монографію О. І. Зозулі "Парламентська реформа в Україні: виклики та перспективи" - Бандурка, О. М.; Bandurka, O. M. (Форум права. - 2023. - № 2(75). - С. 144-146, 2023)
Надана характеристика монографії Зозулі О. І. "Парламентська реформа в Україні: виклики та перспективи" як такої, що є актуальною, підготовленою на достатньому науковому рівні, а її положення та висновки присвячені всебічному дослідженню складної динаміки парламентської реформи в Україні та розумінню викликів і можливостей, які стоять попереду. В роботі висвітлено особливості розбудови парламентаризму як напрямку конституційної реформи у незалежній Україні та актуальні питання парламентської реформи в умовах російсько-української війни. Розглянуто проблеми та шляхи вдосконалення законотворчої та контрольної діяльності Верховної Ради України, засади формування та діяльності тимчасових слідчих комісій Верховної Ради України. Виконано аналіз сучасного стану та проблем правового статусу парламентської опозиції в Україні та європейських країнах, перспектив забезпечення дотримання норм депутатської етики, особливостей конституційно-правового статусу Голови Верховної Ради України та апарату парламенту. Надані пропозиції та рекомендації щодо вдосконалення конституційно-правового статусу та діяльності Верховної Ради України, її органів і народних депутатів України.

The provided characterization of the monograph by O.I. Zozulia "Parliamentary Reform in Ukraine: Challenges and Prospects" is described as relevant, prepared at a sufficient scientific level, with its positions and conclusions dedicated to the comprehensive study of the complex dynamics of parliamentary reform in Ukraine and the understanding of the challenges and opportunities ahead. The work highlights the features of building parliamentarism as a direction of constitutional reform in independent Ukraine and current parliamentary reform issues in the context of the Russian-Ukrainian war. It discusses problems and ways to improve legislative and oversight activities of the Verkhovna Rada of Ukraine, principles of the formation and operation of temporary investigative commissions of the Verkhovna Rada of Ukraine. An analysis of the current state and problems of the legal status of the parliamentary opposition in Ukraine and European countries is provided, as well as prospects for ensuring compliance with the norms of parliamentary ethics, features of the constitutional and legal status of the Chairman of the Verkhovna Rada of Ukraine and the parliament's apparatus. Proposals and recommendations for improving the constitutional and legal status and activities of the Verkhovna Rada of Ukraine, its bodies, and members of the Ukrainian parliament are presented.

Дана характеристика монографии Зозули О. И. "Парламентская реформа в Украине: вызовы и перспективы" как актуальной, подготовленной на достаточном научном уровне, а ее положения и выводы посвящены всестороннему исследованию сложной динамики парламентской реформы в Украине и пониманию вызовов и возможностей. В работе отражены особенности развития парламентаризма как направления конституционной реформы в независимой Украине и актуальные вопросы парламентской реформы в условиях российско-украинской войны. Рассмотрены проблемы и пути усовершенствования законотворческой и контрольной деятельности Верховной Рады Украины, основы формирования и деятельности временных следственных комиссий Верховной Рады Украины. Проведен анализ современного состояния и проблем правового статуса парламентской оппозиции в Украине и европейских странах, перспектив обеспечения соблюдения норм депутатской этики, особенностей конституционно-правового статуса Председателя Верховной Рады Украины и аппарата парламента. Представлены предложения и рекомендации по усовершенствованию конституционно-правового статуса и деятельности Верховной Рады Украины, ее органов и народных депутатов Украины.
Keywords: рецензія; монографія; Зозуля О. І.; Верховна Рада України; парламентська реформа; реформування; review; monograph; Zozulia O. I.; Verkhovna Rada of Ukraine; parliamentary reform; reformation; рецензия; монография; Верховная Рада Украины; Зозуля О. И.; парламентская реформа; реформирование